Upaya Mengurangi Kecemasan Berbicara Di Depan Publik dalam Public Speaking dari Sisi Psikologis dan Praktis - Hamama, Syifa; Ratri, Rose Kusumaning (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2023)
This article aims to explore strategies that are effective in reducing individuals' public speaking anxiety. Anxiety in this context is a psychological challenge that can affect performance and mental well - being. On the other hand, there are psychological strategies, including self - understanding and emotion regulation, as well as practical strategies such as thorough preparation, repeated practice, use of relaxation techniques, and focus on the audience or message. The combination of psychological and practical strategies resulted in a positive impact in holistically reducing anxiety level s. Practical implications involve the development of training programs and psychological interventions to improve public speaking skills. This article contributes to our understanding of how to manage anxiety in public speaking, creating a foundation for thedevelopment of strategies that can be adopted by individuals and public speaking trainers in an effort to improve the quality of communication in public